2020
DOI: 10.5194/acp-20-15191-2020
|View full text |Cite
|
Sign up to set email alerts
|

Ship-based measurements of ice nuclei concentrations over the Arctic, Atlantic, Pacific and Southern oceans

Abstract: Abstract. Ambient concentrations of ice-forming particles measured during ship expeditions are collected and summarised with the aim of determining the spatial distribution and variability in ice nuclei in oceanic regions. The presented data from literature and previously unpublished data from over 23 months of ship-based measurements stretch from the Arctic to the Southern Ocean and include a circumnavigation of Antarctica. In comparison to continental observations, ship-based measurements of ambient ice nucl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
76
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(96 citation statements)
references
References 52 publications
18
76
2
Order By: Relevance
“…In general, the INP concentrations in air masses associated with land are higher than those with a strong marine influence (McCluskey et al, 2018b;Vergara-Temprado et al, 2017;DeMott et al, 2016;Welti et al, 2020). This terrestrialmarine divide is related to the sources in the two environments.…”
Section: The Cloud-phase Feedback and The Importance Of Ice-nucleating Particlesmentioning
confidence: 94%
See 1 more Smart Citation
“…In general, the INP concentrations in air masses associated with land are higher than those with a strong marine influence (McCluskey et al, 2018b;Vergara-Temprado et al, 2017;DeMott et al, 2016;Welti et al, 2020). This terrestrialmarine divide is related to the sources in the two environments.…”
Section: The Cloud-phase Feedback and The Importance Of Ice-nucleating Particlesmentioning
confidence: 94%
“…Further evidence for a strong terrestrial source of INPs in the Arctic was found by Irish et al (2019a), with a correlation between INP concentrations and the time that air spent over bare land during late summer. In addition to mineral dust, which tends to control the INP population only below about −15 • C (Murray et al, 2012), there is evidence that there are strong sources of terrestrial biogenic material active at much warmer temperatures across the Arctic (Tobo et al, 2019;Wex et al, 2019). Terrestrial biogenic material might be associated with sediments from rivers (Tobo et al, 2019) or vegetated areas (Conen et al, 2016;Schnell and Vali, 1976).…”
Section: Inps In the Northern Middle To High Latitudesmentioning
confidence: 99%
“…A wealth of recent studies has substantiated early findings from the 1970s that sea spray aerosol (SSA) particles are able to act as ice-nucleating particles (INPs) in the immersion freezing mode for clouds in the mixed-phase temperature regime between 273 and 235 K (e.g. Bigg, 1973;Schnell and Vali, 1975;Knopf et al, 2011;Wilson et al, 2015;DeMott et al, 2016;Ladino et al, 2016;McCluskey et al, 2017;Creamean et al, 2019;Irish et al, 2019;Welti et al, 2020;Wilbourn et al, 2020;Wolf et al, 2020). As a comprehensive overview of previous investigations, we recommend the compilation in Table 1 by Ickes et al (2020).…”
Section: Sea Spray Aerosol As a Source Of Ice-nucleating Particlesmentioning
confidence: 99%
“…Mason et al, 2015;Ladino et al, 2019;Wex et al, 2019), ship-and aircraft-based measurements (e.g. McCluskey et al, 2018a;Hartmann et al, 2020;Welti et al, 2020), as well as complex laboratory experiments where phytoplankton blooms were simulated in large seawater tanks and wave channels, generating SSA particles by plunging sheets of water or breaking waves (e.g. DeMott et al, 2016;McCluskey et al, 2017;McCluskey et al, 2018b).…”
Section: Sea Spray Aerosol As a Source Of Ice-nucleating Particlesmentioning
confidence: 99%
“…Bigg (1973) collected aerosol samples in Australia, Schnell and Vali (1975) in Huntington Beach (California, US), in the Caribbean off Nassau (Bahamas), and in Vancouver and Nova Scotia (Canada), Rosinski et al (1987) over the Pacific Ocean, and Rosinski et al (1988) in the Gulf of Mexico (GoM). More recently, the ice nucleating abilities of particles present in the Arctic sea surface microlayer (Wilson et al, 2015;Irish et al, 2017Irish et al, , 2019 and the Arctic ambient aerosol were evaluated (DeMott et al, 2016;Creamean et al, 2018;Wex et al, 2019). Similar studies were performed over the eastern Mediterranean by Gong et al (2019), over the Southern Ocean by McCluskey et al (2018) and Welti et al (2020), over the North Atlantic by Wilbourn et al (2020), and over the tropical Atlantic by DeMott et al (2016), Welti et al (2018), Ladino et al (2019), Ladino et al (2020), and Gong et al (2020a).…”
Section: Introductionmentioning
confidence: 96%